The Federalist :a Commentary on the constitution of the United States (Being a collection of essays written in support of the constitution agreed upon September 17, 1787, by the Federal Convention - Alexander Hamilton, John Jay (The Modern Library)
Buku ini mengupas tentang hukum federal dan federalisme di Amerika Serikat.